The non-designer's presentation book : principles for effective presentation design - Williams, Robin, ....- (Berkeley : Peachpit, 2010)
The Non-Designer's Presentation Book by Robin Williams is a book destined to be useful to all presenters, be they beginners, intermediate, or advanced. The author focuses mostly on digital presentations, but takes care to differentiate between a presentation, a speech, and a lecture. A presentation by its very nature implies the use of visual aids - enter Microsoft's PowerPoint, Apple's Keynote, Google's Presently, or OpenOffice's Impress. However, the presenters are not limited to software. They may also use a flip chart, chalkboard, or whiteboard, and "great handouts." What is used depends on the content of the material and the audience. Robin Williams has had years of experience not only writing great books, but also giving presentations - technical, biographical, or theatrical. She has wanted to write this book for years. And we now thankfully have a guide for all of us who wish to be better at sharing our knowledge. She has a knack for turning complicated material into a fascinating yarn.
It is encouraged to be precise as to what we have liked about good presentations and about those that were not so good. By focusing on the specifics of the not so good (monotone and low voice), it is hoped that we can avoid replicating the annoying things and enforce the positive aspects (expressive and humorous). The book guides the reader from how to design slides to discerning the best content for the audience. There are tips galore to avoid pitfalls, from the delivery of a great presentation to designing beautiful and useful slides. The color illustrations pop throughout the book. The best part for me was the way Robin Williams organized the ending. I found that the title of Section IV, Final Thoughts on Presentation Design, encapsulated several points mentioned throughout the book. These are: Learn Your Software; Handouts; Ignore these Rules; and Listen to your Eyes, which includes a quiz on the various points made throughout the book. And finally, there is a Checklist for info; Checklist for slides; and Sources for fonts/images/video/sound. It is emphasized everywhere in the book to spend time outlining your thoughts BEFORE learning the software. The more time spent on the details of a great presentation, the better the chance that it will yield the best outcome. Quoting John Tollett, "Preparation works better than optimism." Buy this book. It's a must-have for all presenters, especially for Apple User Group members who need to make presentations to our groups. I learned a lot from it and expect my next presentation to be unforgettable. In a good way!
Keywords: Presentaties